Rancang Bangun Sistem Informasi Konawe Elektronik Sistem Data (Koneksi Data) dengan Menggunakan Metode Waterfall Model - Resty Saleha; Desri Puspita Sari; La Ode Muhammad Bahtiar Aksara (Publikasi Indonesia, 2023)
The purpose of this study was to design a data management information system at the Konawe District Bappeda Office and to provide convenience for Bappeda in providing a centralized online-based data and information system, so as to facilitate the process of analyzing policy making. The software development model used is the Waterfall Model which emphasizes sequential and systematic phases. The Waterfall model is used in the design of a Data Connection Information System. The research results show that the design of the Data Connection Information System consists of several stages, namely: needs analysis, application design, programming, testing and program installation that produces Village/Kelurahan Monographic Data, OPD Key Performance Indicator Data (IKU), and LPPD OPD Achievement Data. The system was developed using the PHP-based codeigniter framework which integrates all stages into a web-based application.